Preparation of FTO/CU2O Electrode Protected by PEDOT:PSS and Its Better Performance in the Photoelectrocatalytic Reduction of CO2 to Methanol - Sanchez de la Cruz, Pamela Teresa; Irikura, Kallyni [UNESP]; Lachgar, Abdessadek; Cardoso, Juliano Carvalho; Alarcon Cavero, Hugo; Boldrin Zanoni, Maria Valnice [UNESP] (Springer, 2020)
Copper(I) oxide (Cu2O) was electrochemically deposited on fluorine-doped tin oxide (FTO) glass electrode and covered with a thin layer of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS). The electrode was studied in the photoelectrocatalytic reduction of CO2. Methanol was obtained as the major product with a concentration of 460 mu mol L(-1)with a photoconversion yield of 12% after 60 min of reaction under the conditions of UV-Vis (125 W Hg high pressure lamp) and application of 0.0 V vs Ag/AgCl in 3.0 mol L-1 KCl in buffer sodium carbonate/sodium bicarbonate 0.1 mol L(-1)saturated with CO(2)gas. The PEDOT:PSS has led to a significant improvement in CO(2)conversion due to rapid transfer of photogenerated holes. Consequently, the thin layer of PEDOT:PSS also reduces the photooxidation of Cu2O to CuO. The Cu2O/PEDOT:PSS photocatalytic system was found to have excellent photostability. Similar yield of alcohol was observed after reusing the catalyst six times.
Keywords: Photochemical stability; Formation of alcohols; Photoelectroreduction of CO2; Catalyst assembly